The Formation of Ecological and Economic Competences in the Context of the Stable Development of the Carpathian Region - Khymynets, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The paper deals with the peculiarities of the formation of ecological and economic competences at modern school. The paper shows that ecological and economic education is continuous and uninterrupted psychological process which is directed towards the formation of knowledge, culture and consciousness of a person. Attention is paid to the problems of environmental and economic situation in the Carpathian region of Ukraine. Ecological and economic model of education can develop effectively only on the basis of humanistic orientation and innovation potential of the educational institution. The humanization provides increased attention to the individual as a whole, the promotion of its abilities, physical and moral qualities. Modern education aims to form environmentally and economically responsible person, that is ready for the conscious activity on the basis of the gained knowledge and formes behavioral norms and rules concerning the environment. Humanity has the ability to choose either the path of environmental and economic education, or the path of the global catastrophe and self-destruction. Civilized, cultured people are called to protect and multiply the good, by laws and authority to establish the highest spiritual values of the life in the society and public opinion. Only intelligence and environmental and economic culture, that is continuous educational training and educational activity, may generate culture of society, relevant to the permanent development, and transfer its relationships with the environment on the way of intelligent coexistence.